Employee resistance to change : is it the message or the messenger? - Kulkarni, Vaibhavi (London : Indian Institute of Management, Ahmedabad, 2019)
The case revolves around a change initiative introduced in the Indian division of a US-based organization operating in the field of building and composite glass materials. The case has been written from the perspective of Sreenath, who has recently joined as the country head, and has identified four pertinent changes as part of his aggressive growth strategy. The proposed changes pertain to shift in market focus, reorganization of the sales and marketing vertical, revised targets, and revised compensation structure with increase in variable pay. Sreenath's meeting with his core team regarding the proposed changes indicates that he is likely to face resistance during change implementation. The case draws attention to the salience of communication practices surrounding change, and highlights the need to attend to employee perspective during change.
Originally Published InKulkarni, V. (2019). Employee Resistance to Change: Is it the Message or the Messenger? IIMA/COMM0022. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Communication in management -- Case studies; Personnel management -- Case studies